National Estimates of Exposure to Traumatic Events and PTSD Prevalence Using DSM‐IV and DSM‐5 Criteria. Issue 5 (22nd October 2013) - Kilpatrick, Dean G.; Resnick, Heidi S.; Milanak, Melissa E.; Miller, Mark W.; Keyes, Katherine M.; Friedman, Matthew J.
<x xml:space="preserve">Abstract</x> Prevalence of posttraumatic stress disorder (PTSD) defined according to the American Psychiatric Association's Diagnostic and Statistical Manual fifth edition (DSM‐5; 2013) and fourth edition (DSM‐IV; 1994) was compared in a national sample of U.S. adults (N = 2, 953) recruited from an online panel. Exposure to traumatic events, PTSD symptoms, and functional impairment were assessed online using a highly structured, self‐administered survey. Traumatic event exposure using DSM‐5 criteria was high (89.7%), and exposure to multiple traumatic event types was the norm. PTSD caseness was determined using Same Event (i.e., all symptom criteria met to the same event type) and Composite Event (i.e., symptom criteria met to a combination of event types) definitions. Lifetime, past‐12‐month, and past 6‐month PTSD prevalence using the Same Event definition for DSM‐5 was 8.3%, 4.7%, and 3.8% respectively. All 6 DSM‐5 prevalence estimates were slightly lower than their DSM‐IV counterparts, although only 2 of these differences were statistically significant. DSM‐5 PTSD prevalence was higher among women than among men, and prevalence increased with greater traumatic event exposure. Major reasons individuals met DSM‐IV criteria, but not DSM‐5 criteria were the exclusion of nonaccidental, nonviolent deaths from Criterion A, and the new requirement of at least 1 active avoidance symptom.